HYDATID CYST IN A RARE SITE; THE LEFT VENTRICLE - Nadeem Ijaz,; Huma Hanif,; Zahid Rehman ,; Niaz Ali,; Tahir Iqbal,; Imtiaz ur Rehman, (Journal of Ayub Medical College Abbottabad, 2022)
Echinococcosis is a disease that has been affecting human beings since decades and is primarily a zoonotic disease. The larvae of genus Echinococcus causes this disease. The most common sites for these cysts are the lungs and liver. Cardiac hydatidosis is a rare phenomenon and the incidence of such cases is about 1.3%. The case presented is of a 15-year-old boy who would have shortness of breath on exertion and acute right leg pain. To diagnose cardiac variant of the cystic disease, computed topography (CT) and echocardiography were done. Doppler studies confirmed acute limb ischemia. The treatment modality was an open-heart surgery and bilateral embolectomy of the popliteal artery. The patient was discharged to home with albendazole chemotherapy. The study gives an insight into an unusual presentation and successful treatment of cardiac hydatid cyst as well as the associated complications that can be encountered.